Reminiscing and the Passage of Years: Investigating the Role of Affective Autobiographical Memories in Passage of Time Judgments - Kosak, Ferdinand; Kuhbandner, Christof (Frontiers in Psychology, 2021)
Previous research has shown that judgements of the experienced velocity of recent years passing by vary depending on the number of autobiographical memories being activated in the moment of judging. While a body of evidence shows affect to have an impact on both prospective and retrospective judgments on the experience of time for short periods, the effect of valence of memories on the experience of the passage of long intervals has not been examined yet. Thus, we asked 282 people to retrieve five either emotionally positive or negative memories from the last five years before judging the subjectively experienced passage of time of these years. However, positive and negative events differ in some ways beyond valence, e.g. the ascribed impact on the participants’ subsequent lives as well as the stability of ascribed affective intensity: the latter decreased over time for negative but not for positive memories while ascribed impact was markedly higher for positive memories. Results indicate no significant differences between the two conditions, even after controlling for the aforementioned differences. However, exploratory analyses show that participants rate time to have passed faster, the longer the activated memories dated back on average, a result that seems in line with contextual change hypothesis.